circHIPK3 Exacerbates Folic Acid-Induced Renal Tubulointerstitial Fibrosis by Sponging miR-30a - Wu, Yan; Luan, Junjun; Jiao, Congcong; Zhang, Shiwen; Ma, Cong; Zhang, Yixiao; Fu, Jingqi; Lai, En Yin; Kopp, Jeffrey B.; Pi, Jingbo; Zhou, Hua (Frontiers in Physiology, 2022)
Renal tubulointerstitial fibrosis is a common pathological feature of progressive chronic kidney disease (CKD), and current treatment has limited efficacy. The circular RNA circHIPK3 is reported to participate in the pathogenesis of various human diseases. However, the role of circHIPK3 in renal fibrosis has not been examined. In this study, we aimed to determine whether and how circHIPK3 might participate in the pathogenesis of renal fibrosis. Mice received a peritoneal injection of folic acid (250 mg/kg). Of note, 30 days later, renal fibrosis was present on periodic acid–Schiff (PAS) and Masson staining, and mRNA and protein of profibrotic genes encoding fibronectin (FN) and collagen 1 (COL1) were increased. Renal circHIPK3 was upregulated, while miR-30a was downregulated, assessed by quantitative PCR (qPCR) and fluorescence in situ hybridization (FISH). The expression of transforming growth factor beta-1 (TGF-β1) was increased by qPCR analysis, immunoblotting, and immunofluorescence. Renal circHIPK3 negatively correlated with miR-30a, and kidney miR-30a negatively correlated with TGF-β1. Target Scan and miRanda algorithms predicted three perfect binding sites between circHIPK3 and miR-30a. We found that circHIPK3, miR-30a, and TGF-β1 colocalized in the cytoplasm of human tubular epithelial cells (HK-2 cells) on FISH and immunofluorescence staining. We transfected circHIPK3 and a scrambled RNA into HK-2 cells; miR-30a was downregulated, and the profibrotic genes such as TGF-β1, FN, and COL1 were upregulated and assessed by qPCR, immunoblotting, and immunofluorescence staining. Third, the upregulation of circHIPK3, downregulation of miR-30a, and overproduction of profibrotic FN and COL1 were also observed in HK-2 cells exposed to TGF-β1. Finally, renal biopsies from patients with chronic tubulointerstitial nephritis manifested similar expression patterns of circHIPK3, miR-30a, and profibrotic proteins, such as TGF-β1, FN, and COL1 as observed in the experimental model. A feed-forward cycle was observed among circHIPK3, miR-30a, and TGF-β1. Our results suggest that circHIPK3 may contribute to progressive renal fibrosis by sponging miR-30a. circHIPK3 may be a novel therapeutic target for slowing CKD progression.